A growth regime approach to demand, distribution, and employment with endogenous NAIRU dynamics - Hiroshi Nishi (Revue de la Régulation)
This study builds a growth regime model to analyse demand, income distribution, and employment rate. It also examines the causes and effects of the endogenous dynamics of the non-accelerating inflation rate of unemployment (NAIRU) from Régulationist and post-Keynesian perspectives. Specifically, this study (1) explores how demand and distribution regimes are established; (2) identifies the stability conditions for the multi-feedback mechanism among demand, distribution, and employment under different regimes; and (3) reveals how different endogenous degrees of NAIRU affect the dynamic behaviour of macroeconomic variables within a growth regime. We identify four types of growth regimes: two types of demand regimes (i.e. wage-led and profit-led) and two types of distribution regimes (i.e. goods market-led and labour market-led). We also demonstrate that the multi-feedback mechanism among demand, distribution, and employment under different growth regimes needs particular institutional coordination to realise stability. Moreover, we show that a certain endogenous degree of NAIRU may induce perpetual cycles in some growth regimes, whereas the stability of other growth regimes is independent of NAIRU’s endogeneity. Thus, our growth regime approach confirms the primary conclusions of the Régulation theory: an economy has business cycles and growth patterns specific to its institutional structures.